Optimization of a waste polyethylene terephthalate/fly ash hybrid concrete composite in slabs - Nkomo, Nkosilathi Zinti (Vaal University of Technology, 2022)
Cracked concrete slabs are a problem due to several factors such as poor maintenance, insufficient reinforcement or steel corrosion leading to crack propagation. There is a need to increase the load-bearing capacity of concrete slabs and increase their life span. The use of waste Polyethylene Terephthalate (PET) fibres and fly ash in a hybrid composite slab dramatically alleviates the problem of crack propagation and failure sustainably. This study aimed to optimize a waste PET fibre/fly ash hybrid cement composite for use in slabs. This study characterized the raw materials used, including fly ash and aggregates. After that, concrete test specimens were fabricated using the PET fibres and fly ash following the full factorial experimental design. The developed specimens were then tested to ascertain their material strength properties. Model development was carried out using Minitab Software Version 14, and subsequent experimental validation was carried out. After that, the PET and fly ash optimisation for maximum favourable response outcome was carried out. The fly ash was found to belong to the Class F category with particle size ranging from 0.31 μm to 800 μm. The fly ash was mainly spherical and consisted of Ca, Al, P, Si, and trace amounts of Ti and Mg. The spherical shape of the fly ash helped improve the concrete's workability. The river sand had a fineness modulus of 3.69, considered coarse sand. The fine aggregate showed uniform particle size distribution with a uniformity coefficient of 4.007. The coarse aggregate characterisation was carried out and revealed that the aggregate particle size was 13 mm in size. The coarse aggregate had a uniformity coefficient of 4.007, which implied the aggregate was well graded. The coarse aggregate had a high flakiness index of 74.82 % and an acceptable elongation index of 46.72 %. Full factorial methodology experimental design was employed to fabricate the test specimens by simultaneously varying the independent factors to develop a model for overall response variation. The slump value was observed to increase with the addition of fly ash. However, the addition of PET fibre decreased the slump value with incremental amounts of fibre. The combined effect of fibre addition and fly ash showed a general decreasing slump value for all quantities of fly ash content. The compressive strength of PET fibre only composite had maximum strength at 0.5% fibre addition, and the composite with fly ash alone had the maximum compressive strength at 15%. The combined optimum compressive strength for fibre and fly ash was at 0.5 % and 15 %, respectively, with a 15.54 N/mm2. The split tensile strength decreased with an increase in fibre content. However, the fibre provided crack retardation. Fly ash increased the split tensile strength significantly to a peak of 2.35 N/mm2 for 20 % fly ash addition. The combined addition of fibre and fly ash had an optimum split tensile strength of 2.79 N/mm2 at 0.5 % fibre and 20 % fly ash. The addition of fibre had an optimum split tensile strength at 0.5% of 1.82 N/mm2. The fly ash increased the flexural strength, with optimum strength at 15 %. The combined addition of fibre and fly ash created optimum flexural strength at 0.5% and 30 %, respectively. The trend observed by the rebound number followed that of the compressive strength. However, the non-destructive rebound hammer method gave significantly lower strength values than the destructive test method. The addition of fly ash had the effect of lowering the cost of producing the slab. However, the addition of fibres marginally increased the cost. The combined effect of fibre and fly ash resulted in a significant cost saving. Numerical optimisation was carried out concerning the fibre reinforced concrete's fresh and hardened mechanical properties. Predictive modified quadratic equations were developed for slump value, compressive, flexural, split tensile strength and total cost. Analysis of variance test carried out for all the responses indicated that the model could predict the slump value and mechanical properties of the fibre reinforced concrete correctly and effectively with a coefficient of determination in the range of 0.4151 to 0.9467. The developed model can predict the required fibre reinforced fresh and hardened properties in order to assist in decision making in construction in slabs. The optimum constituent combination for maximum mechanical strength at the lowest possible cost was found to be 15.7576 % Fly ash and 0.3232 % PET fibre with optimum responses as shown in Table 4-26. These predictions were validated experimentally, and a good correlation was observed between the actual and predicted values based on the observed standard deviations of 0.1335, 0.031, 0.005, 0.676, 0.02 for compressive strength, flexural strength, tensile strength, slump value and cost, respectively. Concrete slabs were optimised for various possible end uses, and the optimum PET fibre % and fly ash % were ascertained as shown in Table 4-27.
D. Eng. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Fly ash; Polyethylene terephthalate; Fibre; Concrete slabs; Dissertations, Academic -- South Africa.; Concrete slabs.; Composite materials.; Polyethylene terephthalate.; Fly ash -- Testing.; Fibers.